Citizenship, Statelessness, and the Constitution: A Critical Study of Legal Reform and International Obligations - Taufiqurrahman, Taufiqurrahman; Suganda, Atma; Ariyamang, Watcharee (Journal Evidence Of Law, 2025)
The phenomenon of statelessness is a serious challenge for national and international legal systems, especially when a country's constitution is unable to guarantee effective protection of the right to nationality. This article aims to explore the tension between constitutional sovereignty and international obligations in addressing statelessness, as well as analyze how domestic legal frameworks can be reformulated to be more inclusive. Using a normative legal method and a comparative approach, this study examines three jurisdictions—Indonesia, Myanmar, and Latvia—and identifies three patterns of state failure: legitimized legal exclusion, transitional ambiguity, and administrative neglect. The findings suggest that constitutions should be positioned as dynamic legal instruments capable of internalizing international human rights principles, rather than mere expressions of state sovereignty. Through a transformative constitutionalism approach, this article emphasizes the importance of citizenship law reform involving the establishment of independent adjudicative mechanisms and the harmonization of legislation with international conventions. The main contribution of this research is the development of a typological model of state failure and the formulation of a multilevel reform agenda as a foundation for the formulation of more just and accountable legal policies for stateless individuals.